Teachers' and Students' Perceptions of the Use of Learning Media in Improving Swimming Learning Outcomes in Junior High Schools in Cirebon City - Kurniawan, Fajar; Raharjo, Bambang Budi; Rahayu, Tandiyo; Rahayu, Setya (Journal of Ecohumanism, 2025)
This study explores teachers' perceptions of instructional media in swimming education and its role in enhancing students' learning outcomes in junior high schools in Cirebon. Using a qualitative approach, six randomly selected physical education teachers participated in in-depth interviews to share their experiences and insights regarding instructional media integration in swimming lessons. The data were analyzed through thematic analysis to identify recurring patterns and significant themes. The findings reveal that teachers perceive instructional media, such as instructional videos and interactive simulations, as valuable tools for improving students' understanding and motivation in swimming education. Teachers reported that students demonstrated better stroke coordination and higher engagement when media were incorporated into lessons. However, challenges such as limited technological infrastructure, lack of teacher training, and concerns over students' dependency on media were also highlighted. This study contributes to the theoretical discussion on multimodal learning by reinforcing the importance of visual and auditory stimuli in skill acquisition. From a practical perspective, the research underscores the necessity of teacher training programs and improved infrastructure to optimize media use in physical education. Despite its contributions, the study is limited by its small sample size and specific geographic focus. Future research should examine a wider range of participants, including students, and explore the long-term effects of instructional media on skill development. Enhancing media integration strategies can support more effective and engaging swimming education.